Contact restriction time after common nuclear medicine therapies: spreadsheet implementation based on conservative retention function and individual measurements. (1st June 2023) - Broggio, D; Célier, D; Michel, C; Isambert, A
Abstract: The increasing use of new radiopharmaceuticals invites us to reconsider some radiation protection issues, such as the contact restriction time that limits public exposure by nuclear medicine patients. Contact restriction time should be patient specific and conservative, and its assessment made easy for clinicians. Here a method is proposed based on conservative estimation of the whole-body retention function and at least one measurement of the patient's dose rate. Recommended values of the retention function are given for eight therapies: 131 I (Graves' disease, remnant ablation, patient follow-up, meta-iodobenzylguanidine), 177 Lu-prostate-specific membrane antigen and 177 Lu-DOTATATE therapies, and 90 Y and 166 Ho microsphere injection of the liver. The patient line source model for scaling dose rate from one distance to another is included in the restriction time calculation. The method is benchmarked against published values and the influence of the dose rate scaling and whole-body retention function illustrated. A spreadsheet is provided, along with the source code, with recommended values for the eight therapies. The recommended values can be changed as well as the dose rate scaling function, and other radiopharmaceuticals can be included in the spreadsheet provided retention functions are defined.